اتجاهات الشباب نحو داعش وعلاقتها بالمستوى الاقتصادي الاجتماعي دراسة ميدانية على عينة من طلبة جامعة السليمانية - فرج, نجاة محمد (Sulaimani Journal for Humanities, 2025)
This research aims to identify the attitudes of young peopl towards the (ISIS) Represented by students of the University of Sulaymaniy, and for all faculties (scientific, human), male and female. And knowledge of the differences in the attitudes of the students towards the (ISIS) according to the variables of sex and sections (scientific and human), and to know the correlation between the attitudes of the students and their socio-economic status. The researcher used two of the descriptive study entries: Introduction of the documentary literature to organize the sample, and the social survey. The sample of the research was 344 students who were randomly selected for the academic year 2015-2016. Students, which consists of (52) paragraphs distributed on three axes. The first is the definition of a da'ash and its objectives, which include (18) paragraphs, and the second : reasons for the emergence of da'as (16), and the third: the seriousness of the da'ash on the Kurdistan Region included 18 paragraphs, each paragraph five estimates according to the method of Ligert, Applicable to the search sample. After the application of the research tool to students and data collection and treatment statistically using statistical means (Fisher equation, T test, Pearson correlation coefficient, One Way Anova Analysis). The results indicated that there is a negative trend towards the ISIS by the students of the University of Sulaymaniy, and there were no statistically significant differences according to the gender variable (male or female) or according to the specialization (scientific and human). There was no correlation between the socioeconomic levels of the students and their attitudes towards the da'ash, Regardless, the correlation is inversely weak. In other words, the better the economic situation becomes, the more the trend will go on. The correct statement is that the socio- economic situation is not affected at all by an encouraging ISIS.